The Sleep Patterns and Influencing Factors of Chronic Heart Failure Patients in China: A Latent Profile Analysis - Li Y; Li J; Qin J; Zhou S; Gong K (Nature and Science of Sleep)
Yan Li,1,2 Jiamin Li,1,2 Jingwen Qin,1 Sixin Zhou,1,2 Kaizheng Gong1 1Department of Cardiology, Affiliated Hospital of Yangzhou University, Yangzhou University, Yangzhou, People’s Republic of China; 2School of Nursing School of Public Health, Yangzhou University, Yangzhou, People’s Republic of ChinaCorrespondence: Kaizheng Gong, Department of Cardiology, Affiliated Hospital of Yangzhou University, Yangzhou University, No. 368, Hanjiang Middle Road, Yangzhou, 225000, People’s Republic of China, Email yungkzh@163.comPurpose: Sleep problems such as reduced sleep efficiency, difficulty initiating sleep, and increased sleep disturbances significantly affect the quality of life and health status of patients with chronic heart failure (CHF). However, the sleep patterns of CHF patients and their influencing factors need to be further studied. Therefore, this study aimed to explore the latent sleep patterns in patients with CHF and to analyze the factors influencing different sleep patterns.Patients and Methods: A convenience sampling method was adopted to select 290 patients with CHF who were hospitalized in the Department of Cardiology of a tertiary hospital in Yangzhou City, Jiangsu Province, China, from January to August 2024. The investigation utilized a general information questionnaire, the Pittsburgh Sleep Quality Index (PSQI), and the Fear of Progression Questionnaire-Short Form (FoP-Q-SF). Utilizing Mplus version 8.3 for potential profile analysis, the influences on potential categorization were examined through univariate and multivariate logistic regression analyses.Results: The sleep quality score of 290 patients with CHF was (12.00± 3.95). The findings from latent profile analysis indicated that the sleep quality patterns of patients with CHF were categorized into three distinct profiles: relatively good sleep group (n=87, 30.3%), low sleep efficiency-low medication use group (n=160, 54.9%), and sleep disorder-substance dependence group (n=43, 14.8%). Multiple logistic regression analysis showed that age, monthly income, number of hospitalizations for heart failure in a year, number of comorbidities, and fear of progression were influential factors (P < 0.05).Conclusion: Sleep quality among patients with CHF exhibits distinct distributional profiles. Healthcare providers should implement tailored sleep management strategies and psychological interventions, aligning with the sleep patterns and influencing factors specific to patients with CHF. However, it is necessary to note that this study employed a cross-sectional design, and future research could benefit from a longitudinal design.Keywords: chronic heart failure, sleep quality, latent profile analysis, fear of progression, influencing factors